Mental fitness in higher education: Intervention Mapping programme design. Issue 1 (8th April 2020) - O' Brien, Niamh; Lawlor, Martin; Chambers, Fiona; O'Brien, Wesley
Abstract : Purpose: Higher Education Institutions observe that many students are experiencing mental health issues, such as high levels of anxiety and stress. Young adults are recognised as a vulnerable group who carry the burden of mental health problems worldwide. Mental health interventions can be effective in positively influencing students' emotional and behavioural wellbeing. Design/methodology/approach: In the current study, the principles of Intervention Mapping (IM) were applied to guide the development, implementation, and evaluation of a specifically tailored mental health programme for a selected student cohort in a large Higher Education Institute in Ireland. Mixed qualitative (Delphi technique and focus group discussions) and quantitative (survey) data were gathered to gain a broad perspective of mental health concerns and learning needs among a sample of higher education students ( n = 99). Findings: Existing evidence guided by theoretical frameworks were blended to create a specifically tailored mental health programme to meet the needs of higher education students in Ireland. Results indicate that the established six-stages of IM provide an empirical process that has the potential to effectively respond to the mental health needs of students in higher education. IM identifies the priority needs of students in higher education and ensures that suitable behaviour change techniques for mental health are addressed. 10; Originality/value: IM is a suitable method to critically and collaboratively develop a mental health intervention for the overall wellbeing of the general higher education student population, both nationally and globally. 10;